Tooth Abrasion as a Trait of the Human Population of Lepenski Vir - Grga, Đurica (Balcanica - Annual of the Institute for Balkan Studies, 1997)
More than 350 human skeletons were uncovered during excavations carried out in several sites belonging to the culture of Lepenski Vir, dating between the 8th and 6th millennia BC. The skeletons comprise one group, known among experts as the ’Đerdap anthropological series’. Thanks to these discoveries, science is able to learn not only of the material culture of the inhabitants, but, on the basis of the skeletal remains, about the members of the culture as well. The material for the investigation comes from four of the biggest sites on the Yugoslav side of the Danube: Vlasac, Lepenski Vir, Padina and Hajdučka Vodenica. Out of the 350 human skeletons dug up, 133 were used for this analysis, the teeth entirely or partially preserved. A total of 1964 teeth were examined, 889 of the upper jaw and 1075 of the lower jaw.